The Development of Learning Multimedia to Improve English Communication Skills - Leny Meidiantary (JETL (Journal of Education, Teaching and Learning), 2019)
This study aims to find out the development of learning multimedia through multimedia development design with material welcoming guests and registering guests at the Hotel, as well as to see how to improve English communication skills using learning multimedia with research subjects in XI grade of Hospitality Accommodation in Pontianak 5 State Vocational High School study the material. The research method used in this research is the development research method by combining the Borg & Gall development model with the Assure learning design model. Data obtained through interviews, observations and tests applied to the subject of the study. The flow of this research is carried out through three main stages, namely: (1) Product development plan phase which includes needs analysis, learning planning, (2) product development phase, which includes analysis of media forms, outlining media program contents, making flowcharts, collecting materials , making programs and (3) testing and revision stages which included small group trial, initial product revisions, second trial (medium scale), product revisions from the results of the second trial, field trial (large scale). The results of the study showed an increase in the presentation using learning multimedia starting from 2.80 from the value of the small group trial, 3.01 for the second trial value and 3.36 for the trial implementation value. In improving English communication skills, the learning completeness increased from an average value of 69.08 to pretest to 83.50 for the posttest average. This means that the use of learning multimedia can contribute to improving the skills of students communicating English.